2005
DOI: 10.1182/blood-2005-01-0368
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a protective role of the Gardos channel against hemolysis in murine spherocytosis

Abstract: It has been shown that mice with complete deficiency of all 4.1R protein isoforms (4.1-/-) exhibit moderate hemolytic anemia, with abnormal erythrocyte morphology (spherocytosis) and decreased membrane stability. Here, we characterized the Gardos channel function in vitro and in vivo in erythrocytes of 4.1-/- mice. Compared with wild-type, the Gardos channel of 4.1-/- erythrocytes showed an increase in Vmax (9.75 +/- 1.06 vs 6.08 +/- 0.09 mM cell x minute; P < .04) and a decrease in Km (1.01 +/- 0.06 vs 1.47 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 33 publications
(32 reference statements)
1
36
0
Order By: Relevance
“…The Na-H exchange and K-Cl co-transport might be secondarily activated either by possible abnormal functional interactions between membrane proteins and the transmembrane ion transport pathway or by perturbations in signal transduction pathways modulating ion movements through the membrane, as previously described in mouse red cells genetically lacking band 4.1. 10,29 Since the activity of the membrane cation transport pathways is related to cyclic phosphorylation-dephosphorylation events by kinase phosphatases, we evaluated the membrane tyrosine phosphorylation profile in diseased red cells. In diseased red cells, we observed an increase of band 3 tyrosine phosphorylation, most likely due to increased membrane association of Syk and Lyn kinases which have already been reported to tyrosine-phosphorylate band 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Na-H exchange and K-Cl co-transport might be secondarily activated either by possible abnormal functional interactions between membrane proteins and the transmembrane ion transport pathway or by perturbations in signal transduction pathways modulating ion movements through the membrane, as previously described in mouse red cells genetically lacking band 4.1. 10,29 Since the activity of the membrane cation transport pathways is related to cyclic phosphorylation-dephosphorylation events by kinase phosphatases, we evaluated the membrane tyrosine phosphorylation profile in diseased red cells. In diseased red cells, we observed an increase of band 3 tyrosine phosphorylation, most likely due to increased membrane association of Syk and Lyn kinases which have already been reported to tyrosine-phosphorylate band 3.…”
Section: Discussionmentioning
confidence: 99%
“…With this procedure the internal sites for both transport systems were saturated. 10,12,13 The nystatin loading solution contained 70 mmol/L NaCl, 70 mmol/L KCl and 55 mmol/L sucrose. The Na/K pump activity was estimated as the ouabain-sensitive fraction of Na + efflux into a medium containing 130 mmol/L choline chloride and 10 mmol/L KCl.…”
Section: Red Cell Membrane Protein Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…38 Hemolysis may also arise from impaired glucose metabolism, hemoglobin synthesis, or defective erythrocyte membrane permeability. [39][40][41][42] However, it remains largely unknown how these critical proteins are regulated. In the present study, we have shown that inactivation of Rb and E2f8 in erythroid cells synergizes to trigger hemolysis ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, the proper function of Gardos channel is pivotal for the integrity and function of RBCs [75][76][77][78] . Gardos channels are ubiquitously expressed in body tissue 79 and their functionality may depend on intact XK protein.…”
Section: Mls Is a Multisystem Disordermentioning
confidence: 99%